Monetary policy and the persistent aggregate effects of wealth redistribution - Martin Kuncl; Alexander Ueberfeldt (Bank of Canada, 2021)
We identify a sizable wealth redistribution channel which creates a monetary policy trade-off whereby short-term economic stimulus is followed by persistently lower output over the medium term. This trade-off is stronger in economies with more nominal household debt but weakened by a more aggressive monetary policy stance and under price-level targeting. Given this trade-off, low-for-long episodes can lead to persistently depressed output. The mediumterm implications of the wealth redistribution channel rely on the presence of labor supply heterogeneity, which we show both analytically and in the context of an estimated New Keynesian general equilibrium model with household heterogeneity.
Keywords: E21; E50; 330; Monetary policy framework; Monetary policy transmission